The Effects of Coaching, Mentoring, and Counseling on Employee Job Satisfaction - Azzahra, Siti Aisah; Arfian (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Introduction to The Problem: This study aims to analyze the influence of coaching, mentoring, and counseling methods on employee job satisfaction. Purpose : Job satisfaction is a key factor in human resource management that directly impacts employee productivity and retention. Employee development methods such as coaching, mentoring, and counseling play a crucial role in enhancing job satisfaction by fostering both professional growth and personal well-being. Design/methods/approach: The research method used is a literature review of e-journals published in the last five years. Findings : Based on a literature review of various studies, this research demonstrates that coaching, mentoring, and counseling have a positive impact on job satisfaction. The findings reveal that these methods not only provide better career guidance but also increase employee engagement within the organization. Full support from organizations and leaders is essential to ensure the effectiveness of these programs and to deliver optimal outcomes for employees.